Trends in genetic gain for yam in the IITA breeding program - Asfaw, A.; Agre, A.P.; Dieng, I.; Adebola, P.O.; Obidiegwu, J.; Chamba, E.; Darkwa, K.; Otoo, E.; Dansi, A.; Dibi, K.E.B.; Kouakou, A.M.; Asiedu, R. (Wiley, 2024)
Monitoring genetic gain is crucial to ensure breeding programs' effectiveness and identify potential challenges and areas for their improvement. Our study provides a first overview of the trends in genetic gain for tuber yield and disease resistance traits in the IITA's (International Institute of Tropical Agriculture) yam breeding program. We used historical data (2010–2022) from multiple generations of past breeding cycles evaluated at 31 sites in the white Guinea yam (Dioscorea rotundata Poir) breeding pipeline and 28 sites in the water yam (Dioscorea alata L.) breeding pipeline of IITA and its national partners in West Africa. Our result shows positive genetic trends in fresh tuber yield while recording a gain of 1.38% or 99.17 kg ha−1 per year in the white Guinea yam and 2.18% or 252.41 kg ha−1 per year in the water yam breeding pipelines. Genetic trends for virus and anthracnose resistance were in the desired direction but negligible in white Guinea yam, while significant for virus and nonsignificant for anthracnose resistance in water yam. Our findings indicate that while the breeding program has succeeded in enhancing tuber yield, post-harvest tuber dry matter content and disease resistance (yam mosaic virus and anthracnose) did not follow a similar trend in the material being developed. This implies that the yam breeding program needs to strike a balance between various traits, ensuring that increased yield does not come at a cost to food quality or disease resistance. Our results highlight the importance of continually monitoring and assessing the performance of a breeding program and making informed decisions about which traits to focus on for future improvement.